2018
DOI: 10.1063/1.5020426
|View full text |Cite
|
Sign up to set email alerts
|

Using monomer vibrational wavefunctions to compute numerically exact (12D) rovibrational levels of water dimer

Abstract: We compute numerically exact rovibrational levels of water dimer, with 12 vibrational coordinates, on the accurate CCpol-8sf ab initio flexible monomer potential energy surface [C. Leforestier et al., J. Chem. Phys. 137, 014305 (2012)]. It does not have a sum-of-products or multimode form and therefore quadrature in some form must be used. To do the calculation, it is necessary to use an efficient basis set and to develop computational tools, for evaluating the matrix-vector products required to calculate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
89
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 68 publications
(95 citation statements)
references
References 109 publications
(172 reference statements)
6
89
0
Order By: Relevance
“…Forschungsartikel predicted to be even about 7cm À1 lower in frequency, [27,50] as well as the K a = 0 ! 1(2s) transition cannot be observed here.…”
Section: Angewandte Chemiementioning
confidence: 97%
See 4 more Smart Citations
“…Forschungsartikel predicted to be even about 7cm À1 lower in frequency, [27,50] as well as the K a = 0 ! 1(2s) transition cannot be observed here.…”
Section: Angewandte Chemiementioning
confidence: 97%
“…Thetwo AS tunneling levels are also denoted as (1s) and (2s) state.R ecent experimental [29,31,[43][44][45] and theoretical studies, [27,50] showed that the IC tunneling splitting can be dramatically increased upon vibrational excitation. Thetwo AS tunneling levels are also denoted as (1s) and (2s) state.R ecent experimental [29,31,[43][44][45] and theoretical studies, [27,50] showed that the IC tunneling splitting can be dramatically increased upon vibrational excitation.…”
Section: Forschungsartikelmentioning
confidence: 99%
See 3 more Smart Citations